TRENDS OF LUNG FUNCTION INDICES, ARTERIAL BLOOD OXYGEN SATURATION AND PULSE RATE AMONG THE FIRST AND THIRD TRIMESTER PREGNANT WOMEN IN ADDIS ABABA, ETHIOPIA - D, Haile; Y, Abebe (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACT: OBJECTIVE: Comparative analysis of the effects of middle-level altitude pregnancy on lung function indices, blood oxygen saturation and pulse rate as a function of gestational weeks. STUDY DESIGN: This is a Cross-sectional descriptive study conducted in Tikur Anbessa hospital, a tertiary university hospital and Lideta Health Center a public health center located in Addis Ababa, Ethiopia. Participants: 123 pregnant women including 40 in their first and 83 in their third trimester RESULTS: maternal height was positively correlated with FVC and FEV1 but not with PEFR (r=0.68 ; p<0.01). BMI and FEV1% were also positively and negatively correlated in normal and obese subjects respectively. As term approaches, there is a decreasing pattern of PEFR, IC, VT, ERV, (p< 0.005) and hence FRC. However, pulse rate, VE and BF had shown a rising trend. On the other hand, FEV1%, VC, and TLC didn’t change significantly. Chest size had no statistically significant effect on most of the indices. Minimal coffee intake habit and having more children were shown to have desirable pregnancy outcomes. CONCLUSIONS: Based on the present study it is concluded that at moderate altitude, as pregnancy proceeds, some lung function indices like tidal volume and breathing frequency show an increasing tendency unlike most of the static lung function parameters. We recommend that pregnant women should be guided through the predictable physiologic and emotional changes that occur during pregnancy and help them develop coping life style strategies. KEY WORDS: Peak expiratory flow rate, lung function indices, pulse rate, SaO2 , body mass index, chest size, middle-level altitude, first and third trimester. (Ethiopian Journal of Reproductive Health 2016; 8:30–44)